Slang in Tiktok Comments on Juliana Marins’ Posts - Putra, Arvi Sukmana; Supri, Ida Zuraida (Universitas Galuh, 2025)
This research aims to investigate the characteristics and functions of slang words used in the comment sections of international TikTok posts by Juliana Marins. The method applied is qualitative descriptive, based on Moleong (2017). Data were collected by reading the comments of international netizens on TikTok, gathering relevant slang expressions, analyzing and classifying them into various morphological categories, as well as examining their functions and drawing conclusions. The data were taken from several TikTok comments, using Allan and Burridge’s (2006) theory to analyze the types of slang, and Mattiello’s (2008) theory to examine their functions. The findings reveal that the morphological processes of the slang words include Clipping (28%), Blending (17%), Acronyms (23%), Reduplication (5%), Borrowing (7%), Semantic Shift (11%), and Compounding (7%). In terms of creativity, only 45% of the slang—particularly Clipping and Blending—were considered creative. However, regarding function, only 30% of the slang words were used to express identity, as only 3 out of 10 words analyzed served that purpose.